Пристрої рідинного контуру у плівковому витратомірі - Теплюх, З.; Парнета, О. (Видавництво Національного університету «Львівська політехніка», 2003)
Influance of filmformer circuit elements on the operation and metrological characteristics of film flowmeters is analysed and ways of their improvement are offered.